Prefrontal Cortex Oxygenation During Endurance Performance: A Systematic Review of Functional Near-Infrared Spectroscopy Studies - De Wachter, Jonas; Proost, Matthias; Habay, Jelle; Verstraelen, Matthias; Díaz-García, Jesús; Hurst, Philip; Meeusen, Romain; Van Cutsem, Jeroen; Roelands, Bart (Frontiers in Physiology, 2021)
Introduction: A myriad of factors underlie pacing-/exhaustion-decisions that are made during whole-body endurance performance. The prefrontal cortex (PFC) is a brain region that is crucial for decision making, planning and attention. PFC-oxygenation appears to be a mediating factor of performance-decisions during endurance performance. Nowadays, there is no general overview that summarizes the current knowledge on how PFC-oxygenation evolves during whole-body endurance performance and whether this is a determining factor. Methods: Three electronic databases were searched until for studies assessing PFC-oxygenation, through NIRS, during endurance performances. Primary outcome measures where Oxygenated- ([HbO2)]) and deoxygenated- ([HHb]) hemoglobin concentrations to express PFC-oxygenation. Results: 28 articles where included, 10 assessing prefrontal oxygenation through a maximal incremental test (MIT) and 18 using endurance tasks at workloads ranging from low- to supramaximal intensities. Within MIT-studies an increase in [HbO2] was found until the respiratory compensation point (RCP), after which HbO2 decreased in 4 studies, reached a steady state in 4 studies and increased in 1 study until exhaustion and all studies found a decrease or steady state in [HHb] from the start until RCP and an increase until exhaustion. Regarding (non-incremental) endurance tasks, a general increase in PFC-oxygenation was found up to vigorous intensities, at which a steady state was reached. At near to maximal intensities the increase in oxygenation and maintenance of the steady state could not be retained, resulting in PCF-deoxygenation. Discussion/Conclusion: MIT-studies show that a cerebral oxygenation threshold is present at the RCP, there PFC-oxygenation increases until this threshold, whereafter, steady state was reached or HbO2 declined. This study shows the results from MIT are transferable to non-incremental endurance exercise. HbO2 increases during low- and moderate- until vigorous intensity exercise, where HbO2 reaches a steady state. Furthermore, the cerebral oxygenation threshold can be found at the verge between vigorous and near maximal intensity. During endurance exercise at near to maximal intensities or higher, PFC-oxygenation increases until exceeding this threshold, resulting in a decrease in PFC-oxygenation until exhaustion. The focus of future research should be on whether maintaining/improving PFC-oxygenation can improve endurance performance and if PFC-oxygenation has a role in other performance limiting factors.